Adsorption mechanism on metal organic frameworks of Cu-BTC, Fe-BTC and ZIF-8 for CO2 capture investigated by X-ray absorption fine structure. Issue 67 (30th June 2016) - Du, Meng; Li, Lina; Li, Mingxing; Si, Rui
Abstract : XAFS analysis demonstrates the physical driving force, plus minor chemical transformation for the CO2 adsorption mechanism by MOFs. Abstract : Three different commercial metal–organic frameworks (MOFs) of Cu-BTC, Fe-BTC and ZIF-8 have been characterized by multiple techniques including CO2 adsorption/desorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray absorption fine structure (XAFS). Particularly, the MOFs powders were sealed inside quartz sample tubes for each step of CO2 adsorption/desorption, and were sequentially measured for XAFS to identify the short-range structural evolutions on investigated metals (Cu, Fe, Zn). According to the data analyses on X-ray absorption near edge spectroscope (XANES) and extended X-ray absorption fine structure (EXAFS), we can demonstrate that both electronic and local structures of MOFs were almost unchanged between fresh samples and those under the activated/adsorbed/desorbed conditions. This indicates that the CO2 adsorption of MOFs is mainly governed by the physical driving force. On the other hand, the chemical transformation, i.e. elimination of water in MOFs structure by the activation (13.3 kPa, 473 K, 12 h), was found for Cu-BTC only.